Aḥmad al-Ghazālī’s al-Tajrīd fī Kalimat al-Tawḥīd: “A Primer on the Statement of Tawḥīd” - Lumbard, Joseph E. B. (Journal of Sufi studies, 2024)
This article presents an introduction to and the first complete English translation of Aḥmad al-Ghazālī’s (d. 517/1123 or 520/1126), al-Tajrīd fī kalimat al-tawḥīd, his most widely received Arabic text. The title has a double entendre, meaning both “A Primer on the Statement of Tawḥīd,” and “Disengaging Through the Statement of Tawḥīd.” It is designed to serve both purposes. The first half provides a spiritual typography, juxtaposing “the people of grace” (ahl al-faḍl) to “the people of justice” (ahl al-ʿadl). The former are those who maintain their covenant with God and follow the Prophet Muhammad. The latter are those who break the covenant and follow Iblīs. The second half guides aspirants through the levels of spiritual development and the corresponding modes of remembrance (dhikr), detailing three modes of dhikr – lā ilāha illa Llāh (No god, but God), Allāh, and huwa huwa (He, He). These correspond to three levels within the human being, the heart (al-qalb), the spirit (al-rūḥ), and the secret (al-sirr). The goal is to provide an overview of the means whereby one can disengage from the blameworthy inclinations of their soul through the progressive levels of dhikr until the secret predominates over the spirit and the spirit predominates over the heart, such that one is able to focus solely upon God.